Oral health literacy: An approach to end oral health disparities - Amandeep Chopra; N C Rao; Nidhi Gupta; Shelja Vashisth (Wolters Kluwer Medknow Publications, 2013)
Oral health literacy is the degree to which individuals have the capacity to obtain, process, and understand basic health information and services needed to make appropriate oral health decisions. Studies have revealed that literacy skills are strong predictor of individual's health status than age, income, employment status, education level, and racial or ethnic group. Dentist and dental staff are in unique position to help patients with low oral or general health literacy, thus empowering them to play active role in their oral healthcare. This review article introduces some of the key concepts and practical aspects of oral health literacy.